NAVIGATING CAREER SUCCESS: HOW CAREER COMMITMENT SHAPES SELF-EFFICACY AND CAREER RESILIENCE FOR SUBJECTIVE CAREER SUCCESS - Bhawna; Sanjeev Kumar Sharma; Dr. Renu Sharma (Tourism and Hospitality Management, 2024)
Purpose– This study examines the subjective dimension of career success in the dynamic global tourism industry, specifically the relationship between Career Commitment (CC) and Subjective Career Success (SCS). It uses a serial mediation framework with self-efficacy (SE) and career resilience (CR) as mediators and focuses on tourism professionals. Research methodology – We developed a theoretical serial mediation model to investigate this relationship. We conducted regression analysis using SPSS version 25 and AMOS (the Process Macro model 6) to test our proposed hypotheses. A total of 357 employees from various tourism-related organizations participated in this research. Findings – Employees who invested in their careers reported higher satisfaction with SCS in their working lives. Independently and consecutively, SE and CR influenced the association between CC and SCS. Research implications and Originality – The implications of this research extend to individuals and tourism organizations. For individuals, it provides a deeper understanding of how CC, SE and CR interact to manage the complexities of the tourism industry and promote professional success. For organizations, it highlights the importance of promoting CC through effective career development initiatives that can lead to a competent and motivated workforce, which ultimately increases employee engagement and retention.